2007
DOI: 10.1063/1.2778423
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated hydride anion clusters

Abstract: On the basis of density functional theory ͑DFT͒ and high level ab initio theory, we report the structures, binding energies, thermodynamic quantities, IR spectra, and electronic properties of the hydride anion hydrated by up to six water molecules. Ground state DFT molecular dynamics simulations ͑based on the Born-Oppenheimer potential surface͒ show that as the temperature increases, the surface-bound hydride anion changes to the internally bound structure. Car-Parrinello molecular dynamics simulations are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 74 publications
(12 reference statements)
1
26
0
Order By: Relevance
“…coarser fast Fourier transform grids) was used to improve the speed of the calculations, requiring a higher energy cutoff than the default to avoid simultaneously reducing the accuracy of the interatomic force calculations. DFT has been successfully applied to a wide variety of solid-state hydrides and hydrogen storage reactions 6,9,[17][18][19][20][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , however, there are far fewer studies of liquid complex hydrides 21,50 . To study the bulk liquid behavior of the four complex hydrides under a range of thermal conditions, we perform canonical (NVT) Born-Oppenheimer AIMD simulations at 300 K, 500 K and 1000 K. For each compound and temperature, we perform three runs beginning from the solid structure with varied initial velocities to sample a greater portion of phase space (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…coarser fast Fourier transform grids) was used to improve the speed of the calculations, requiring a higher energy cutoff than the default to avoid simultaneously reducing the accuracy of the interatomic force calculations. DFT has been successfully applied to a wide variety of solid-state hydrides and hydrogen storage reactions 6,9,[17][18][19][20][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , however, there are far fewer studies of liquid complex hydrides 21,50 . To study the bulk liquid behavior of the four complex hydrides under a range of thermal conditions, we perform canonical (NVT) Born-Oppenheimer AIMD simulations at 300 K, 500 K and 1000 K. For each compound and temperature, we perform three runs beginning from the solid structure with varied initial velocities to sample a greater portion of phase space (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, static Density Functional Theory (DFT) does not allow for the exploration of the dynamics of liquid-state vibrations or diffusion that occur at high temperatures. Non-zero temperature ab initio molecular dynamics (AIMD), where the interatomic forces that govern atomic motion are determined via DFT, has been used to investigate diffusion in solid NaAlH 4 17 , as well as structural and vibrational properties of hydride clusters 18 and to predict solid-state transformations in LiBH 4 19 . AIMD has also been demonstrated recently in liquid state studies of Li 2 NH 20 and Li 4 BN 3 H 10 21 , where it has been used to to probe structural, diffusive and vibrational characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its well-established use in water cluster studies in general, Swart [33] demonstrated the validity of DFT for H + affinity of solvated anions, and B3LYP/6À311++G** underwent further benchmarking against high-level MP2 for (H -)(H 2 O) n clusters by Lee et al [8]. While DFT with a large basis is certainly a usable model for these systems, it does underestimate slightly the strength of a dihydrogen bond compared to MP2.…”
Section: Methodsmentioning
confidence: 99%
“…Many PES local minima exist for (H -)(H 2 O) 4 [8]. The global minimum (by MP2) has Cs symmetry, denoted here as h-4wCs (cf.…”
Section: N =mentioning
confidence: 99%
See 1 more Smart Citation